Production of Zirconium Aluminides by Self-Propagating High-Temperature Synthesis; Key Engineering Materials; Vol. 769 : High Technology: Research and Applications (HTRA 2017) - Dolmatov O. Yu. Oleg Yurevich; Kolyadko D. K. Daniil Konstantinovich; Pimenov N. O. Nikita; Chursin S. S. Stanislav Sergeevich (2018, 2018)
Title screen